Phytophthora infestans RXLR effector SFI5 requires association with calmodulin for PTI/MTI suppressing activity. Issue 4 (22nd June 2018) - Zheng, Xiangzi; Wagener, Nadine; McLellan, Hazel; Boevink, Petra C.; Hua, Chenlei; Birch, Paul R. J.; Brunner, Frédéric
Summary: Pathogens secrete effector proteins to interfere with plant innate immunity, in which Ca 2+ /calmodulin (CaM) signalling plays key roles. Thus far, few effectors have been identified that directly interact with CaM for defence suppression. Here, we report that SFI5, an RXLR effector from Phytophthora infestans, suppresses microbe‐associated molecular pattern (MAMP)‐triggered immunity (MTI) by interacting with host CaMs. We predicted the CaM‐binding site in SFI5 using in silico analysis. The interaction between SFI5 and CaM was tested by both in vitro and in vivo assays. MTI suppression by SFI5 and truncated variants were performed in a tomato protoplast system. We found that both the predicted CaM‐binding site and the full‐length SFI5 protein interact with CaM in the presence of Ca 2+ . MTI responses, such as FRK1 upregulation, reactive oxygen species accumulation, and mitogen‐activated protein kinase activation were suppressed by truncated SFI5 proteins containing the C‐terminal CaM‐binding site but not by those without it. The plasma membrane localization of SFI5 and its ability to enhance infection were also perturbed by loss of the CaM‐binding site. We conclude that CaM‐binding is required for localization and activity of SFI5. We propose that SFI5 suppresses plant immunity by interfering with immune signalling components after activation by CaMs.